Shariah-Compliant Housing: Opportunities and Challenges in Modern Markets - Noorsidi Aizuddin Mat Noor; Farhana Diana Deris; Mustafa Omar; Hamdi Abdul Hamid; Afizan Mokhtar (Indonesian Journal of Islamization Studies, 2024)
This study examines the market potential and challenges of Shariah-compliant housing, which follows Islamic principles by avoiding interest (riba), gambling (maysir), and excessive uncertainty (gharar). With the global Muslim population growing and demand for Islamic value-aligned products increasing, there is a notable gap in awareness and understanding of Shariah-compliant housing among buyers and investors. Focusing on Malaysia, where the Muslim population is substantial and Islamic financial infrastructure is advanced, the study employs a mixed-method approach. Surveys of 150 Muslim respondents assess consumer preferences, while interviews with industry experts explore supply-side challenges. Findings indicate strong interest in Shariah-compliant housing, with 78% willing to pay a premium. However, barriers such as limited awareness, inadequate Shariah-compliant financing, and unclear regulations remain. The study suggests that addressing these issues through education, clearer regulations, and alternative financing is essential for market growth.